Temperature and water activity effects on production of T-2 and HT-2 by Fusarium langsethiae strains from north European countries - Medina, Angel; Magan, Naresh (Elsevier, 2011)
This study has examined the effect of ecophysiological factors, water activity (aw, 0.995-0.90) and temperature (10-37°C), on the T-2 and HT-2 toxins production by Fusarium langsethiae. Two dimensional profiles for optimum and marginal conditions have been built for two strains from each of four northern European countries (UK, Norway, Sweden, Finland) on an oat-based medium. This showed thatthe optimum aw and temperature conditions for T-2+HT-2 production was between 0.98-0.995, and 20-30°C respectively. Kruskal-Wallis analysis of ranks showed a statistically significant differences between the different aw levels examined (P<0.001) but no significant effect of the temperatures examined. The ratio of HT-2/T-2 was investigated and non-uniform distribution of HT-2 toxin was found under different ecological conditions. No statistically significant differences were found for the mean toxin production between strains from the different countries. Intra-strain differences in toxin production was only found for those from Finland (P-value=0.0247). The growth/no growth and toxin/no toxin conditions in relation to awxtemperature have been constructed for the first time. This knowledge will be useful in developing prevention strategies to minimise T-2 and HT-2 toxin contamination by strains of F. langsethiae on important small grain cereal